Breeding for resistance to Striga and Alectra in cowpea - Singh, B.B.; Emechebe, A.M. (1991)
An outline is given of the progress made in a systematic breeding programme set up in Nigeria to develop improved cowpea cultivars with combined resistance to Striga gesnerioides and Alectra vogelii along with multiple disease and insect resistance. Several sources of resistance to both parasitic weeds have been identified. Of these, B301, a land race from Botswana has shown complete resistance to S. gesnerioides and A. vogelii. This was crossed with a susceptible cultivar, IT84S-2246-4, which is resistant to aphids, bruchids, thrips and 10 diseases and has a high yield potential. The F1 plants were back-crossed with cv. IT84S-2246-4 and segregating populations were screened for resistance to S. gesnerioides, A. vogelii and various insects and diseases. Several F6 breeding lines have now been developed which look very similar to cv. IT84S-2246-4, with combined resistance to S. gesnerioides, A. vogelii, aphids, bruchids, thrips and a variety of diseases Parasitic plant